THE ROLE OF THE AUTHENTIC MATERIALS IN IMPROVING COMMUNICATIVE COMPETENCE OF ESP LEARNERS - Kuchkarova, Mukhabbat (Журнал иностранных языков и лингвистики, 2021)
One of the main elements of the lesson is listening of a new material, which includes the meaning of the text or dialogue envisaged by the curriculum for this discipline. The main requirement for the lessons of explanation of the new material is the conscious assimilation of the material. In order to achieve this and to help students to take the next step in learning a foreign language, it is necessary to carefully explain the terms and concepts. For this, the teacher must use modern innovativetechnologies. One of the most important factors in today's pandemic situation is to provide students with listening comprehension in the distance learning process.